Tìm x biết: 1-2x<7
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\left|7x+3\right|=66\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}7x+3=66\\7x+3=-66\end{cases}}\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}7x=63\\7x=-69\end{cases}}\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}x=9\left(N\right)\\x=-\frac{69}{7}\left(L\right)\end{cases}}\)
Vậy...
b) \(\left|5x-2\right|\le0\)
mà \(\left|5x-2\right|\ge0\)
\(\Rightarrow\)\(\left|5x-2\right|=0\)
\(\Leftrightarrow\)\(5x-2=0\)
\(\Leftrightarrow\)\(x=\frac{2}{5}\) (loại)
Vậy...
\(x.\left(x-\frac{1}{7}\right)\left(\frac{1}{9}+x\right)< 0\)
có 4 TH ( Trường hợp)
TH1: \(\hept{\begin{cases}x>0\\x-\frac{1}{7}>0\\\frac{1}{9}+x< 0\end{cases}\Leftrightarrow\hept{\begin{cases}x>0\\x>\frac{1}{7}\\x< -\frac{1}{9}\end{cases}}}\)( vô lí)
TH2:\(\hept{\begin{cases}x>0\\x-\frac{1}{7}< 0\\\frac{1}{9}+x>0\end{cases}\Leftrightarrow\hept{\begin{cases}x>0\\x< \frac{1}{7}\\x>-\frac{1}{9}\end{cases}\Leftrightarrow}0< x< \frac{1}{7}}\)
TH3:\(\hept{\begin{cases}x< 0\\x-\frac{1}{7}>0\\\frac{1}{9}+x>0\end{cases}\Leftrightarrow\hept{\begin{cases}x< 0\\x>\frac{1}{7}\\x>-\frac{1}{9}\end{cases}}}\)(vô lí )
TH4:\(\hept{\begin{cases}x< 0\\x+\frac{1}{7}< 0\\\frac{1}{9}-x< 0\end{cases}\Leftrightarrow\hept{\begin{cases}x< 0\\x< -\frac{1}{7}\\x>\frac{1}{9}\end{cases}}}\)(vô lí)
KL: 0<x<1/7
b) \(\frac{\left(4-x\right)}{2x}-\frac{1}{5}>0\)đk: \(x\ne0\)
<=> \(\left(4-x\right).5-2x.1>0\)
<=> \(20-5x-2x>0\)
<=> \(20-7x>0\)
<=> \(20>7x\Leftrightarrow x< \frac{20}{7}\)
a) <=> 2x - 1 = 0 hoặc 5x + 2 = 0
<=> 2x = 1 hoặc 5x = -2
<=> x = \(\frac{1}{2}\) hoặc x = \(-\frac{2}{5}\)
b) <=> 3/7 . (1 + 1/x) = 1/4
=> 1 + 1/x = 7/12 <=> 1/x = -5/12
<=> -5/-5x = -5/12 <=> -5x = 12
<=> x = \(-\frac{12}{5}\)
c) Dễ thấy 3x + 5 > 2x - 3
Để (3x + 5)( 2x - 3) < 0 thì 3x + 5 > 0 và 2x - 3 < 0
<=> x > -5/3 và x < 3/2
Vậy \(-\frac{5}{3}< x< \frac{3}{2}\)
a) (2x-1).(5x+2) = 0
\(\Leftrightarrow\) 2x-1 = 0 hoặc 5x+2 = 0
\(\Leftrightarrow\) 2x = 1 hoặc 5x = -2
\(\Leftrightarrow\) x = \(\frac{1}{2}\) hoặc x = \(\frac{-2}{5}\)
b) \(\frac{3}{7}+\frac{3}{7}:x=\frac{-1}{2}-\left(\frac{-3}{4}\right)\)
\(\frac{3}{7}+\frac{3}{7}:x=\frac{-1}{2}+\frac{3}{4}\)
\(\frac{3}{7}+\frac{3}{7}:x=\frac{1}{4}\)
\(\frac{3}{7}:x=\frac{1}{4}-\frac{3}{7}\)
\(\frac{3}{7}:x=\frac{-5}{28}\)
\(x=\frac{3}{7}:\frac{-5}{28}\)
\(x=\frac{-12}{5}\)